Digital Transformation and Total Quality Management as Moderators: Implications for the Financial Performance of Micro, Small, and Medium Enterprises (MSME) - Niken Kusumawardani; Kamadie Sumanda Syafis (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2025)
The worldwide COVID-19 pandemic has profoundly changed many facets of life, including how businesses operate. Among the most impacted industries, Micro, Small, and Medium Enterprises (MSME) must adapt to these changes. One of the adaptive strategies adopted by MSME is incorporating digital technologies into their operational procedures. Restrictions on face-to-face interactions have compelled many MSME to transition to online buying and selling activities. This shift requires business owners to be prepared for digitalization as part of the new normal. With digital transformation acting as a moderating variable, this research attempts to investigate also evaluate the impact of Total Quality Management (TQM) on the financial performance of MSME. The research focuses on MSME located in the banana chips industrial center in Bandar Lampung City. The sample comprises MSME actively involved in digital marketing and transactions. Data were collected through a questionnaire distributed via Google Forms. The results showed that TQM significantly and positively affects the financial performance of MSME. Additionally, it has been demonstrated that digital transformation successfully modifies the correlation between TQM and financial performance.